Patient-Reported Outcomes of Visual Disturbances with a Trifocal Intraocular Lens: A Meta-Analysis - Dagny Zhu; Suyen Karki; Mukesh Dhariwal; Erkki Soini; Christian Asseburg (Ophthalmology and Therapy)
Abstract Introduction Diffractive trifocal intraocular lenses (IOLs) provide good vision at distance, intermediate, and near, but can also cause positive dysphotopsias. This meta-analysis pooled published evidence on visual disturbances after bilateral implantation of the PanOptix (TFNTXX) IOL for patients undergoing cataract surgery. Method A systematic literature search was conducted in PubMed and congress presentations from April 2021 to December 2022 to identify studies with patient-reported outcomes on the incidence of visual disturbances (starbursts, halos, glare) post bilateral implantation of PanOptix IOL during cataract surgery. Random-effects meta-analysis was performed to generate pooled proportions for patient-reported visual disturbances with a 95% confidence interval [CI]. Results Eleven unique studies were included, spanning 580 patients with bilateral implantation of PanOptix IOL from 10 countries with 1 to 12 months follow-up. In summary, 33.6% of patients with bilateral PanOptix implantation experienced glare, 43.9% experienced halos, and 30.4% experienced starbursts. Among these patients, small percentages reported severe glare (2.9%), severe halos (5.4%), and severe starbursts (3.4%). Only 0.8%, 1.4%, and 2.6% of patients found glare, halos, and starbursts, respectively, to be very bothersome. Conclusion Halos are the most frequently reported visual disturbances. However, the likelihood of experiencing severe and/or very bothersome visual disturbances (halos, glare, starbursts) is approximately 5% and 3%, respectively, after bilateral implantation of PanOptix IOL. These findings should inform clinical decision-making and treatment choices when selecting the most appropriate IOL implant for cataract surgery.